The Short-Term Economic Consequences of COVID-19: Occupation Tasks and Mental Health in Canada - Louis-Philippe Béland; Abel Brodeur; Derek Mikola; Taylor Wright (Institute of Labor Economics (IZA), 2020)
In this paper, we document the short-term impact of COVID-19 on labour market outcomes in Canada. Following a pre-analysis plan, we investigate the negative impact of the pandemic on unemployment, labour force participation, hours and wages in Canada. We find that COVID-19 had drastic negative effects on labour market outcomes, with the largest effects for younger, not married, and less educated workers. We investigate whether the economic consequences of this pandemic were larger for certain occupations. We then built indices for whether (1) workers are relatively more exposed to disease, (2) work with proximity to coworkers, (3) are essential workers, and (4) can easily work remotely. Our estimates suggest that the impact of the pandemic was significantly more severe for workers more exposed to disease and workers that work in proximity to coworkers, while the effects are significantly less severe for essential workers and workers that can work remotely. Last, we rely on a unique survey, the Canadian Perspective Survey, and show that reported mental health is significantly lower among the most affected workers during the pandemic. We also find that those who were absent form work because of COVID-19 are more concerned with meeting their financial obligations and with losing their job than those who remain working outside of home, while those who transition from working outside the home to from home are not as concerned with job loss.
Keywords: I15; I18; J21; 330; COVID-19; unemployment; wages; remote work; essential workers; exposure to disease